Incoming medical students' knowledge of and attitudes toward people with substance use disorders: Implications for curricular training. Issue 4 (2nd October 2021) - Moses, Tabitha E.; Chammaa, May; Ramos, Rafael; Waineo, Eva; Greenwald, Mark K.
Abstract: Background: Medical students may be in an ideal position to identify patients with substance use disorders (SUDs) and provide them with information about harm reduction and treatment options. Specific education regarding opioid use disorder (OUD) and naloxone during undergraduate medical training may help students identify these patients and decrease their own negative attitudes toward patients with OUD. To plan for curriculum development, this study aimed to understand baseline knowledge and attitudes among students entering medical school. Methods : During orientation, all first-year medical students (Class of 2023) were asked to complete a survey that explored their previous experiences in healthcare and with SUDs as well as their attitudes toward opioid overdose and patients with SUDs. We administered the Opioid Overdose Knowledge Scale (OOKS), Opioid Overdose Attitudes Scale (OOAS), Medical Conditions Regard Scale (MCRS), and Naloxone Related Risk Compensation Beliefs (NaRRC-B). Results : 266 students (89.6% of the class) completed the survey. Generally, these students were relatively proficient in opioid overdose knowledge, but did not feel they were competent enough to respond to an overdose. Attitudes toward patients with SUDs were mixed. Approximately half of the students thought naloxone distribution should be unrestricted, but many were uncertain whether naloxone receipt would deter individuals from seeking treatment or increase opioid use. Students' previous experiences in healthcare (e.g., employment) results in significantly different knowledge and attitudes toward opioid overdose response. Conclusions : These incoming medical students have greater healthcare experience and level of opioid overdose knowledge than the general population, but still harbor significant misinformation and stigma toward patients with SUDs. These findings provide a foundation upon which to tailor didactic efforts, starting early in medical school, so that graduating physicians can be adequately prepared for clinical care.